2023
DOI: 10.1021/acs.jmedchem.2c02068
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Selectivity of Pharmacological Inhibitors of DYRK and CLK Protein Kinases

Abstract: Dual-specificity, tyrosine phosphorylation-regulated kinases (DYRKs) and cdc2-like kinases (CLKs) play a large variety of cellular functions and are involved in several diseases (cognitive disorders, diabetes, cancers, etc.). There is, thus, growing interest in pharmacological inhibitors as chemical probes and potential drug candidates. This study presents an unbiased evaluation of the kinase inhibitory activity of a library of 56 reported DYRK/CLK inhibitors on the basis of comparative, side-by-side, catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 175 publications
3
26
0
Order By: Relevance
“…Intermediate activity (IC 50 : 0.1−1.0 μM) was observed with 6-benzo(1,2,3)thiadiazol-6-yl (3,18,33), 2-methyl-benzothiazol-6-yl (4,19,34), 2,3-dihydro-benzofuran-5-yl (7,22,37), and N1methylated indazol-5-yl (12,27,42). High kinase inhibitory activity (IC 50 < 0.1−0.2 μM) was observed with the following heteroaryl systems: 5-benzodioxol-5-yl (1, 16, 31), benzothiazol-6-yl (2,17,32), benzoxazol-6-yl (6,21,36), benzimidazol-5-yl (8,23,38), N1-methylated benzimidazol-6-yl (9,24,39), indazol-5-yl (11,26,41), and N2-methylated indazol-5-yl (13,28,43). The high potency of these heterocycles was associated with the possibility of forming a strong H-bond linking Leucine 241 and a nitrogen or an oxygen atom at position A of the benzodioxol-5-yl, benzothiazol-6-yl, benzoxazol-6-yl, benzimidazol-5-yl, N1-methylated benzimidazol-6-yl, indazol-5-yl, and N2-methylated indazol-5-yl, as illustrated with the molecular docking of compound 32 within the ATP-binding pocket of DYRK1A (see below).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intermediate activity (IC 50 : 0.1−1.0 μM) was observed with 6-benzo(1,2,3)thiadiazol-6-yl (3,18,33), 2-methyl-benzothiazol-6-yl (4,19,34), 2,3-dihydro-benzofuran-5-yl (7,22,37), and N1methylated indazol-5-yl (12,27,42). High kinase inhibitory activity (IC 50 < 0.1−0.2 μM) was observed with the following heteroaryl systems: 5-benzodioxol-5-yl (1, 16, 31), benzothiazol-6-yl (2,17,32), benzoxazol-6-yl (6,21,36), benzimidazol-5-yl (8,23,38), N1-methylated benzimidazol-6-yl (9,24,39), indazol-5-yl (11,26,41), and N2-methylated indazol-5-yl (13,28,43). The high potency of these heterocycles was associated with the possibility of forming a strong H-bond linking Leucine 241 and a nitrogen or an oxygen atom at position A of the benzodioxol-5-yl, benzothiazol-6-yl, benzoxazol-6-yl, benzimidazol-5-yl, N1-methylated benzimidazol-6-yl, indazol-5-yl, and N2-methylated indazol-5-yl, as illustrated with the molecular docking of compound 32 within the ATP-binding pocket of DYRK1A (see below).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As a result, we initiated molecular modeling to gain a better understanding of the interactions (Figure ). The binding mode of Leucettinib-92 ( 32 ) was investigated based on the co-crystal structure of Leucettine-41 in complex with DYRK1A (PDB code: 4AZE) (briefly described in the Supplementary Information of ref ). In the adenine region, the benzothiazol-6-yl acts as a hinge binder through a strong 2.1 Å hydrogen bond between the scaffold’s nitrogen and the backbone’s N–H of Leu241 in addition to a weak hydrogen bond between the polarized C7–H of the scaffold and the backbone’s carbonyl of Glu239.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the search for, optimization and biological characterization of DYRK1A inhibitors has been quite intense during the past few years (see reviews in refs and ). A comparative study of 56 reported DYRKs/CLKs inhibitors has been published recently which describes the potency and selectivity of most of the reported inhibitors …”
Section: Introductionmentioning
confidence: 99%